Aloe barbadensis polymeric acetylated mannan modified by self-assembly through a pervaporation aloe polysaccharide membrane: Safety evaluation and tail fin regeneration in zebrafish - Di Li; Jiajie Deng; Mengmeng Wang; Haiyang Yin; Jinzi Chen; Weijie Xu; Xiaofeng Guo; Xueli Tong; Ding Ye; Jiejing Li (Carbohydrate Polymer Technologies and Applications)
Aloe vera has a remarkable anti-inflammation effect in wound healing and other skin disorders. Its bioactivity is mainly attributed to the polysaccharides. However, the clinical applications of aloe vera are considerably restricted by the low efficacy of its extracts. To increase its bioactivity, it is necessary to develop de novo techniques for extracting and modifying aloe polysaccharides. This study used pervaporation to perform self-assembly of aloe vera polysaccharides, leading to the production of aloe barbadensis polymeric acemannan 2 (ABPA2). ABPA2 was associated with increasing of acytel functional groups compared to ABPA1. Electron microscopic analysis showed ABPA2 was able to form supporting membrane. The safety of ABPA2 was evaluated through acute and chronic toxicity experiments. Functionally, it was able to induce zebrafish tail fin healing after wounding. The effects were in all likelihood ascribed to its ability to induce proliferation and macrophage extravasation in wounded tail fin. By applying RNA-seq, it showed that ABPA2 triggered multiple types of cells differentiated and proliferation mainly through regulating genes expression of extracellular matrix. After all it was able to activate mitochondrial biogenesis through regulating mechanotransduction of calcium. These findings warrant a further chemical-biological investigation in mammalian wound healing.